2021
DOI: 10.1101/2021.02.26.433092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis of chemical and biological problems associated with browning agents used in aquatic studies

Abstract: Inland waters receive and process large amounts of colored organic matter from the terrestrial surroundings. These inputs dramatically affect the chemical, physical, and biological properties of water bodies, as well as their roles as global carbon sinks and sources. To understand the complex changes associated with allochthonous inputs, experiments are needed. However, manipulative studies, especially at ecosystem scales, require large amounts of dissolved organic matter with optical and chemical properties r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
1
8
1
Order By: Relevance
“…Other factors and processes will likely affect the in situ photodegradation of DOM (75–77), but high laboratory photodegradation rates suggest that there is a high potential for photodegradation of the added humic substances, at least of the colored portion. While the samples in our Baltic Sea study are different, previous work found very little degradation of HuminFeed when kept in the dark, but observed CDOM and DOC decreases accompanied by increases in particulate matter, when exposed to visible light (68).…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…Other factors and processes will likely affect the in situ photodegradation of DOM (75–77), but high laboratory photodegradation rates suggest that there is a high potential for photodegradation of the added humic substances, at least of the colored portion. While the samples in our Baltic Sea study are different, previous work found very little degradation of HuminFeed when kept in the dark, but observed CDOM and DOC decreases accompanied by increases in particulate matter, when exposed to visible light (68).…”
Section: Discussioncontrasting
confidence: 81%
“…7 and Table 1). These trends were again consistent with the addition of humic substances to the mesocosm, and may suggest an increase in aromaticity when humic substance was added (65) and a decrease in aromaticity during subsequent in situ degradation of the added humic substance (79,83), as HuminFeed is abundant in aromatic compounds (68). The SUVA 254 values became similar again between the control and humic‐amended mesocosms toward the end of the amendment experiment (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations